Service quality dimensions, perceive value and customer satisfaction: ABC relationship model testing - Yeop Yunus Nek Kamal, Ismail Azman, Juga Zubrina Ranee, Ishak Salomawati, (N/A, 2009)
Service quality dimensions, perceive value and customer satisfaction: ABC relationship model testing by Yeop Yunus Nek Kamal, Ismail Azman, Juga Zubrina Ranee, Ishak Salomawati,